2017
DOI: 10.1038/s41598-017-04988-9
|View full text |Cite
|
Sign up to set email alerts
|

Achieving low-emissivity materials with high transmission for broadband radio-frequency signals

Abstract: The use of low-emissivity (low-e) materials in modern buildings is an extremely efficient way to save energy. However, such materials are coated by metallic films, which can strongly block radio-frequency signals and prevent indoor-outdoor wireless communication. Here, we demonstrate that, when specially-designed metallic metasurfaces are covered on them, the low-e materials can remain low emissivity for thermal radiation and allow very high transmission for a broad band of radio-frequency signals. It is found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…[ 9 ] To mitigate this drawback, recent studies have suggested sub‐wavelength patterning of low‐emissive films to preclude barrier properties of uniform silver films in the low RF frequency range by virtue of disconnected repeating pattern of Ag islands. [ 4 ] However, with the advances in fifthg‐generation (5G) telecommunication there is a pressing need to develop versatile and flexible designs capable of operating in the higher frequency range extending to 100 GHz. [ 9,10 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] To mitigate this drawback, recent studies have suggested sub‐wavelength patterning of low‐emissive films to preclude barrier properties of uniform silver films in the low RF frequency range by virtue of disconnected repeating pattern of Ag islands. [ 4 ] However, with the advances in fifthg‐generation (5G) telecommunication there is a pressing need to develop versatile and flexible designs capable of operating in the higher frequency range extending to 100 GHz. [ 9,10 ]…”
Section: Introductionmentioning
confidence: 99%
“…
and include conductive oxides such as indium thin oxide (ITO), aluminum zinc oxide (AZO), vanadium oxide (VO 2 ), and dielectric-metal-dielectric (DMD) layer stacks. [1][2][3][4][5][6][7][8] While considerable development of various low-emissive coatings has been realized, the use of highly conductive materials for near-infrared (NIR) control results in the blockage of RF signals which makes the implementation of these devices in the smart city environment dubious. [9] To mitigate this drawback, recent studies have suggested sub-wavelength patterning of low-emissive films to preclude barrier properties of uniform silver films in the low RF frequency range by virtue of disconnected repeating pattern of Ag islands.
…”
mentioning
confidence: 99%
“…In this regard, low emissive coatings have been extensively studied and include conductive oxides such as indium thin oxide (ITO), aluminum zinc oxide (AZO), vanadium oxide (VO 2 ), and dielectric-metal-dielectric (DMD) layer stacks. [1][2][3][4][5][6][7][8] While considerable development of various low-emissive coatings has been realized, the use of highly conductive materials for near-infrared (NIR) control results in the blockage of RF signals which makes the implementation of these devices in the smart city environment dubious. 9 To mitigate this drawback, recent studies have suggested subwavelength patterning of low-emissive films to preclude barrier properties of uniform silver films in the low RF frequency range by virtue of disconnected repeating pattern of Ag islands.…”
Section: Introductionmentioning
confidence: 99%
“…9 To mitigate this drawback, recent studies have suggested subwavelength patterning of low-emissive films to preclude barrier properties of uniform silver films in the low RF frequency range by virtue of disconnected repeating pattern of Ag islands. 4 However, with the advances in 5G telecommunication there is a pressing need to develop versatile and flexible designs capable of operating in the higher frequency range extending to 100 GHz. 9,10 With the introduction of metasurfaces, 2D periodic structures comprising sub-wavelength inclusions capable of engineering unconventional optical and radio frequency (RF) properties, the possibility of designing novel materials such as invisibility cloaks has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed a growing interest in thin metallic nano-films that can simultaneously offer high electrical conductivity and optical transparency, owing to their promising potential in realizing various optically transparent electromagnetic (EM) devices and low-emissivity materials. In this regard, conductive oxides (e.g., indium tin oxide (ITO), aluminum-doped zinc oxide (AZO)) and dielectric-metal-dielectric (DMD) designs (usually comprising silver nano-films) have been extensively studied [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] for a variety of applications. These include lowemissivity optical coatings [1-3, 16, 19, 20], transparent conductive oxides (TCOs) in photovoltaic devices [2][3][4], transparent circuit components [4], antennas [5], metamaterials [7-10, 17, 20, 21], and various flexible devices and sensors [11,12,18].…”
Section: Introductionmentioning
confidence: 99%